ANALISIS MAJAS DALAM BUKU OVERTHINKING IS MY HOBBY, AND I HATE IT KARYA ALVI SYAHRIN - Wary, Fransiska Febrivaras; Sulissusiawan, Ahadi; Amir, Amriani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
This study aims to analyze the use of figures of speech such as contrast, emphasis, comparison, and satire in the book Overthinking Is My Hobby, and I Hate It by Alvi Syahrin. The method used in this study is a descriptive method with a qualitative form. The data source in this study is the book Overthinking Is My Hobby, and I Hate It by Alvi Syahrin. The research data consists of text quotations containing figures of speech according to the predetermined categories. The data collection technique used is an indirect technique in the form of documentary study. In this study, the types of figures of speech found include 25 metaphors, 20 personifications, and 7 hyperboles. The figures of emphasis found in this study include 14 paradoxes and 11 antitheses. The figures of speech of emphasis found in this study include 21 parallelisms and 12 repetitions. The figures of speech of irony found in this study include 2 sarcasms and 1 irony. The results of this study can serve as a reference for readers, academics, and educators in understanding and appreciating the use of figurative language in literary works.